(untitled) (Itinerarios Educativos, 2024)
This paper is situated in the debates around learning processes. We place ourselves in a perspective of analysis that reflects on everyday situated practice and we understand that all knowledge construction processes occur in a relational framework that provides conditions of possibility for learning, including historical practices, artefacts and routines that can be accumulated and used later. From a historical ethnographic perspective, we analyse the modalities of knowledge construction that occur in Antarctica. We investigate the practices developed by scientist and technician personal, considering the circulation of knowledge, routines and use of artefacts and the development of communities of practice. We assume that all activity, including learning, is situated in and made of relationships between people, contexts and practices. In this way, we analyse how these relationships are configured considering the different backgrounds and trajectories of the subjects, variables such as the ‘Antarctic experience’, the number of research campaigns carried out, among others.